A Novel Testis-Specific Gene, Ccdc136, Is Required for Acrosome Formation and Fertilization in Mice. (October 2016) - Geng, Qiang; Ni, Liwei; Ouyang, Bin; Hu, Yanhua; Zhao, Yu; Guo, Jun
Testis-specific genes are essential for the spermatogenesis in mammalian male reproduction. In this study, we have identified a novel testis-specific gene, Ccdc136 (coiled-coil domain containing 136), from the results of high-throughput gene expression profiling in the developmental stage of mouse testes. Ccdc136 was conserved across species in evolution. Quantitative real-time polymerase chain reaction and Western blot analyses showed that Ccdc136 messenger RNA and protein were extraordinarily expressed in mouse testes, which was first presented at postnatal 3 week and increased in an age-dependent manner before adulthood. Immunofluorescence staining revealed that CCDC136 protein was most abundantly located in the acrosome of round spermatids and elongating spermatids within seminiferous tubules of the adult mouse testes. To investigate the function of Ccdc136 in mouse testes, we generated the Ccdc136 -knockout mice using Cas9/RNA-mediated gene targeting technology. Interestingly, we found Ccdc136 −/− males were infertile, due to severe defect of disrupting acrosome formation. The expression levels of proteins (SPACA1 and PICK1) involved in acrosome formation were significantly downregulated in the testes of Ccdc136 −/− mice than wide-type mice. Moreover, in vitro fertilization assay revealed that anti-CCDC136 antibody could remarkably inhibit fertilization, suggesting CCDC136 also plays an important role in fertilization. All of these demonstrated the essential role of CCDC136-mediated acrosome formation in spermatogenesis and fertilization, which might also provide new insight into the genetic causes of human infertility.